2004
DOI: 10.1103/physrevb.70.024504
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-substitution effect on the electronic properties ofMgB2single crystals

Abstract: The electronic properties of the carbon substituted MgB2 single crystals are reported. The carbon substitution drops Tc below 2 K. In-plane resistivity shows a remarkable increase in residual resistivity by C-substitution, while the change of in-plane/out-of-plane Hall coefficients is rather small. Raman scattering spectra indicate that the E2g-phonon frequency radically hardens with increasing the carbon-content, suggesting the weakening of electron-phonon coupling. Another striking C-effect is the increases … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
128
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(149 citation statements)
references
References 46 publications
20
128
1
Order By: Relevance
“…The fact that there is no correlation of H c2 (0) with ρ across numerous samples leads to the suggestion that the measured resistivity is ρ π , while H c2 (0) is determined by σ-band scattering 15 (ρ σ ), with the magnitude of ρ σ being 125 to 165 µΩ cm. 6 However, to explain the observed form of H c2 (T), 16 and of irradiation, 14 and alloying with carbon, 4 is similar to that seen in many A15 and ternary boride superconductors, 17 it is not necessary to invoke interband scattering to explain such a reduction in T c . Smearing of the peak, and reduction of the density of states at the …”
Section: -10mentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that there is no correlation of H c2 (0) with ρ across numerous samples leads to the suggestion that the measured resistivity is ρ π , while H c2 (0) is determined by σ-band scattering 15 (ρ σ ), with the magnitude of ρ σ being 125 to 165 µΩ cm. 6 However, to explain the observed form of H c2 (T), 16 and of irradiation, 14 and alloying with carbon, 4 is similar to that seen in many A15 and ternary boride superconductors, 17 it is not necessary to invoke interband scattering to explain such a reduction in T c . Smearing of the peak, and reduction of the density of states at the …”
Section: -10mentioning
confidence: 99%
“…Of particular interest is the large increase in H c2 that results from alloying with carbon, [1][2][3][4] and also, in the case of thin films, from disorder and possibly impurities that are introduced during deposition. 5 It has been shown that in Three MgB 2 thin films (A, S, and PB), all grown on sapphire substrates, were used for this study, while PA was used earlier.…”
Section: Introductionmentioning
confidence: 99%
“…A reduction of γ was reported after neutron irradiation [23,24] or can be achieved by carbon doping [30], but it seems to be always accompanied by an increase of the upper critical field B c2 (which further enhances B ⊥ c2 and enlarges the application range). Although experimentally difficult, the influence of such a "pure" change of anisotropy on J c is demonstrated in Fig.…”
Section: Consequences/strategymentioning
confidence: 99%
“…Reduction of coherence length due to enhanced impurity scattering is considered to contribute to the enhancement of H c2 [30][31][32][33] . Furthermore, flux pinning strength was found to be enhanced by carbon substitution 6,19,20,23,24 .…”
Section: Introductionmentioning
confidence: 99%